” The Lust of Dog” - Bekmurodova F. U. (Open Academia, 2024)
This article studies literal interpretation of “The lust of dog” through stories. The symbol of dog is differentiated in several Uzbek and English stories. The notion “the lust of dog” is discussed and explained differently in different stories, their writing styles are different, however symbol of dog is given with deep meaning that make every reader think thoroughly and deeply. Through the theme “the lust of dog” there is given both connotative and denotative meanings which help readers to differentiate the characters.
Keywords: symbols; negative connotation; lust; faith